Evaluation of controller medication efficiency in patients with moderate and severe uncontrolled asthma - P. A. Selivanova (Бюллетень сибирской медицины, 2009)
Evaluation of efficiency of controller medication (combination of fluticasone propionate and Salmeterol) in 40 patients (age from 18 to 65 years) with moderate (n = 15) and severe (phenotype brittle n = 10, asthma with fixed obstruction n = 15) uncontrolled asthma was evaluated in open prospective trial. It was observed, that all patients with moderate asthma achieved control criteria (GINA, 2006) to 12th week of treatment with combination of fluticasone propionate and Salmeterol. Improvement of clinical-functional indexes was observed in patients with severe asthma to 24th week of therapy. 5 patients with brittle asthma achieved controlled and partly controlled asthma to 24th week therapy. Controlled asthma was not reach through the patients with fixed obstruction asthma, whereas increase of clinical-functional parameters was observed, usage of inhaled combined therapy allowed us to reduce oral steroids dose in 4 patients of this group.